Some problems and prospects of aphakia intraocular correction in cataract phacoemulsification (Ukrainian Journal of Ophthalmology, 2026)
The analysis of scientific literature on intraocular correction of aphakia has been carried out. There were marked the progress, achievements and failures of researchers at all stages of cataract surgery, which along with the introduction of new operation methods carried out the search and development of new models of intraocular lens, the main criteria of which had been designated by S. N. Fedorov. The important properties of the IOL are considered to be ideal biocompatibility, biostability, perfect transparency, defined borders of refractive index, lightness in the aqueous humor, elasticity with shape memory without generating optical aberrations, providing contrast quality, preservation of color vision, good vision of object details at different distances and under different illuminance along with high visual acuity that approaches IOL to the natural lens of the healthy eye. There were examined the main types of IOL models implanting at present, their advantages and disadvantages, properties and design features among which there are IOLs with accommodative effect, toric, multifocal and aspheric IOLs, lenses with coated optics and chromatic component, simple and stable fixation in the posterior chamber in place of natural lens. Thus, these areas are based on the principles of bionics, so borrowing in nature the ways to improve the methods of intraocular correction look promising on the grounds that the evolutionary nature has eternity and researches are strictly limited in time.
Keywords: cataract; intraocular correction; problems and prospects; principles of bionics